Pregnancy rate in Hanwoo cows after timed artificial insemination using different sperm concentrations - Sung-Sik Kang; Sang-Rae Cho; Ui-Hyung Kim; Yonghwan Kim; Seok-Dong Lee; Myung-Suk Lee; Eunju Kim; Jeong-Il Won; Shil Jin; Hyoun-Ju Kim; Sungwoo Kim; Sun-Sik Jang; et al. (The Korean Society of Animal Reproduction and Biotechnology, 2024)
Background: Sperm quality and the number of sperm introduced into the uterus during artificial insemination (AI) are pivotal factors influencing pregnancy outcomes. However, there have been no reports on the relationship between sperm concentration at AI and sperm quality in Hanwoo cattle. In this study, we examined sperm quality and pregnancy rates after AI using sperm inseminated at different concentrations. Methods: We evaluated the motility, viability, and acrosomal membrane integrity of sperm at different concentrations (10, 15, 18, and 20 million sperm/straw) in 0.5-mL straws. Subsequently, we compared the pregnancy rates after AI with different sperm concentrations. Results: After freeze-thawing, sperm at the assessed concentrations showed similar viability and acrosomal membrane integrity. After AI, cattle in the 10 million group had significantly lower pregnancy rates compared to those in the 18 and 20 million groups. Conversely, there were no statistically significant variances observed between cattle in the 10 and 15 million groups. Conclusions: Sperm at concentrations of 10, 15, 18 and 20 million per straw exhibited comparable motility, viability, and acrosomal membrane integrity. However, a concentration of at least 18 million sperm per straw is required to achieve a consistent rate of pregnancy rate in Hanwoo cattle after AI.